Jupyter Notebook: система интерактивных научных вычислений - Якимчик, А.И. (Геофизический журнал, 2019)
Jupyter Notebook ― is a web-appendix which allows writing and supplying comments a code to Python in interactive regime. It is an exclusive method to make experiments and studies and intercommunicate with others. Many research people use this calculative medium in their works more often. The main factors of growing popularity of programming language Python and project Jupyter are characterized in brief.